PENERAPAN PENDEKATAN SAINTIFIK DENGAN MEDIA MUATAN DALAM PENINGKATAN PEMBELAJARAN BILANGAN BULAT PADA SISWA KELAS IV SDN 2 KARANPOH TAHUN AJARAN 2015/2016 - Wulansari, Monik (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: THE APPLICATION OF SCIENTIFIC APPROACH USING MUATAN MEDIA IN IMPROVING LEARNING ABOUT INTEGERS FOR THE FOURTH GRADE STUDENTS OF SDN 2 KARANGPOH IN ACADEMIC YEAR 2015/2016. The objectives of this research are to describe the steps, to improve learning about integers, and to describe the problems and solutions in the implementation of scientific approach using muatan media for the fourth graders of SDN 2 Karangpoh in the academic year of 2015/2016. This research is collaborative Classroom Action Research (CAR). Subjects of the research were fourth grade students of SDN 2 Karangpoh totaling 23 students. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. The results showed that the application of scientific approach using muatan media can improve learning about integers for the fourth grade students SDN 2 Karangpoh the academic year 2015/2016. Keywords: scientific approach, muatan media, learning, integers Abstrak: PENERAPAN PENDEKATAN SAINTIFIK DENGAN MEDIA MUATAN DALAM PENINGKATAN PEMBELAJARAN BILANGAN BULAT PADA SISWA KELAS IV SDN 2 KARANGPOH TAHUN AJARAN 2015/2016. Tujuan penelitian: mendeskripsikan langkah-langkah, meningkatkan pembelajaran bilangan bulat, mendeskripsikan kendala dan solusi penerapan pendekatan saintifik dengan media muatan pada siswa kelas IV SDN 2 Karangpoh tahun 2015/2016. Penelitian ini merupakan penelitian tindakan kelas (PTK). Subjek penelitian adalah siswa kelas IV SDN 2 Karangpoh berjumlah 23 siswa. Teknik pengumpulan data: tes, observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan penerapan pendekatan saintifik dengan media muatan dapat meningkatkan pembelajaran bilangan bulat pada siswa kelas IV SDN 2 Karangpoh Tahun Ajaran 2015/2016. Kata Kunci: Pendekatan Saintifik, Media Muatan, Pembelajaran, Bilangan Bulat